The Application of Providing Analysis Based on Durian Seeds to Improve Protein Intake and Hemoglobin Levels of School Children - Oppusunggu, Riris (Journal of Saintech Transfer, 2020)
School-age children are at high risk of anaemia, because of their low haemoglobin levels due to lack of iron intake. Anaemia causes pain and death, inhibits brain development, motor, mental, intelligence and physical growth, decreased physical abilities, pale faces which will reduce enthusiasm and learning achievement of school children. The purpose of this study was to determine the effect of giving lemuru fish sausage made from durian seeds on protein intake and haemoglobin levels in children with anaemia. This type of research is a quasi-experimental, namely the pre-test design and post-test experiment. Lemuru fish sausage made from durian seeds was given every day for 30 days to 30 school-age children in SD Negeri Jati Sari Lubuk pakam City, Deli Serdang Residence. Measurement of Haemoglobin and food consumption (energy, protein, vitamin C and iron) was carried out before and after the intervention. The results showed that most of the intake of energy, vitamin C and iron in school children was in the <100% category. The mean Haemoglobin before the intervention was 10.9 g / dl; after the intervention, the mean Haemoglobin was 12.1 g / dl. The mean increase in hemoglobin 1.2 g / dl was statistically significant (p-value = 0.000). It has been recommended to increase the time to intervene and use iron status indicators in other studies.